The drowned : a novel - Banville, John (Hanover Square Press, 2024)
"He had seen drowned people. A sight not to be forgotten." 1950s, rural Ireland. A loner comes across a mysteriously empty car in a field. Knowing he shouldn't approach but unable to hold back, he soon finds himself embroiled in a troubling missing person case, as a husband claims his wife may have thrown herself into the sea. Called in from Dublin to investigate is Detective Inspector Strafford, who soon turns to his old ally--the flawed but brilliant pathologist Quirke--a man he is linked to in increasingly complicated ways. But as the case unfolds, events from the past resurface that may have life-altering ramifications for all involved.